Toxic Masculinity in the Jane Campion’s The Power of the Dog - Nurfitriah, Anissa; Hidayat, Syarif; Sulaeman, Karina A; Hariyana, Agustinus; Beresaby, Rheinatus A (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
This study aims to analyze The Power of the Dog (2021) movie script. This research uses a qualitative method using theory of toxic masculinity from Terry A. Kupers to analyze the characters in this movie script by Jane Campion. The aim of this research is to answer two problems of the studies: 1) How is toxic masculinity reflected in The Power of the Dog movie script? 2) How are the impacts of toxic masculinity reflected in The Power of the Dog movie script? The results of this study found four traits of Toxic Masculinity in the characters, there are: 1) Domination; dominate and control over others, 2) Misogyny; hatred and disdain a woman, 3) Homophobia; insult a feminine guy and reject anything feminine, 4) Violence; slap animals, threaten, and even murder. Furthermore, it is also found the impacts of toxic masculinity in the character in The Power of the Dog (2021) movie script, including ;1) Depression, loneliness and isolation, 2) Denial, displacement, reaction formation as defense mechanisms. Based on this research, the movie script of The Power of the Dog represents toxic masculinity through the characters and represents its impacts of toxic masculinity.